1993
DOI: 10.1177/0038038593027004005
|View full text |Cite
|
Sign up to set email alerts
|

Relative Merits: Family Culture and Kinship in Small Firms

Abstract: Small firms are saturated with the ideology of the family. For some, the notion of the `family firm' conjures up an image of harmony at the workplace; moreover, it is seen to serve as an important source of flexibility. Others, however, view it as little more than a cover-up of exploitative practices which are believed to be dominant in small firms. Using an ethnographic approach, this article explores in detail how the notion of the family is actually operationalised at the level of the workplace. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
154
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 5 publications
4
154
0
1
Order By: Relevance
“…The consequent task, often undertaken by women, of organizing communication in extended families is also facilitated by the success of the firm (de Lima, 2000;Johnson, 2000;Ram & Holliday, 1993).…”
Section: The Profits Of Kinshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequent task, often undertaken by women, of organizing communication in extended families is also facilitated by the success of the firm (de Lima, 2000;Johnson, 2000;Ram & Holliday, 1993).…”
Section: The Profits Of Kinshipmentioning
confidence: 99%
“…The reasons are obvious. When kinship position takes priority over experience and capability, a certain cost is a breach in the link between performance and rewards (Belshaw, 1965;Ram & Holliday, 1993). A heavier cost can be the promotion of incompetents who cannot be dismissed (Lomnitz & Pérez-Lizaur, 1987, p. 112;Whyte, 1996).…”
mentioning
confidence: 99%
“…(58) found that family business that promotes close relationships will inspire employee loyalty to be strong, and it will result in a greater performance (59). While the family business is giving more confidence to the employees of a business family members that are more committed (58,60,61) and work harder (62). In Javanese culture has the value of tatag, which is depicting pertinacious in stance or consistent to act cautiously, to the challenge without any sense of doubt and ojo kuminter who showed humility of Javanese to want to continue to learn, and still feel less intelligent (39).…”
Section: Entrepreneurial Learning In Javanese Family Businessmentioning
confidence: 99%
“…Despite the acknowledged importance of family and kinship ties for the survival of immigrant firms (Ram 1992;Ram and Holliday 1993;Anthias and Mehta 2003;Estrada 2016), the nature of this family support has been underresearched, although there are some notable exceptions, such as Song (1995Song ( , 1997Song ( , 1999 or Marger (2001). Given that migrant enterprises are generally in a position of higher vulnerability in the market than non-migrant firms, they are more likely to rely on the informal and cheap labour of family members (Ram 1992;Sanders and Nee 1996), accompanied by an emphasis on collective orientation of goals for migrant families (Valdez 2016).…”
Section: The Role Of Children In Immigrant Family Businessesmentioning
confidence: 99%